Economic theory and the developing countries - Dasgupta, Ajit Kumar (New York : St. Martin's Press, 1974)
This book analyses economic problems of the developing countries within a unified framework of economic theory. It is intended both as a text and reference book on the economics of development at the undergraduate level
Includes bibliographical references and index.
rpm 11/07/2017
Loans
Keywords: Economic development; Developing countries